1998
DOI: 10.1515/jpme.1998.26.5.384
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cardiolipin antibody and anti-cardiolipin beta-2-glycoprotein I antibody in patients with recurrent fetal miscarriage

Abstract: To elucidate the association between anticardiolipin antibody (aCL-Ab) or anti-cardiolipin beta-2-glycoprotein I-antibody (aCL-beta-2-GP I-Ab) and recurrent fetal miscarriage, the positive rates of aCL-Ab were assessed in 667 patients with recurrent fetal miscarriages and those of aCL-beta-2-GP I-Ab were assessed in 208 patients. The rates were then compared with the control group. The positive rate of aCL-Ab in the patients group (17.4%) was significantly higher than that in the control group (4.0%). The rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
0
16
0
2
Order By: Relevance
“…Second, a relationship was found between antiphospholipid antibodies and second trimester losses among Japanese women in one study [38].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Second, a relationship was found between antiphospholipid antibodies and second trimester losses among Japanese women in one study [38].…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, Higashiro et al [38] reported a significant difference in the prevalence of ACL between cases and controls: 17.4% versus 4.0%. Furthermore, ACL was significantly more common in women with a history of second and third trimester losses.…”
Section: Review Of the Selected Articlesmentioning
confidence: 86%
“…58,61,62 The ORs for elevated anticardiolipin antibodies and lupus anticoagulants were 3.40 and 2.97, respectively. [63][64][65][66][67][68][69] However, pooled data on lupus anticoagulants indicated significant heterogeneity (p = 0.04). Sensitivity analysis was performed.…”
Section: Early Pregnancy Lossmentioning
confidence: 99%
“…Several authors underlined the role of the antiphospholipid syndrome (APS) in the pathophysiology of RPL [36][37][38][39][40][41][42][43][44][45][46][47][48]. To confirm this point, actually adverse pregnancy outcome is considered as one of the diagnostic criteria of APS (Table 1) according to the guidelines of the International Society of Thrombosis and Haemostasis and the American Rheumatology Association [49,50].…”
Section: Acquired Thrombophiliamentioning
confidence: 99%